Correlation of right frontal hypoperfusion and urinary dysfunction in iNPH: A SPECT study - Sakakibara, Ryuji; Uchida, Yoshitaka; Ishii, Kazunari; Kazui, Hiromitsu; Hashimoto, Masaaki; Ishikawa, Masaaki; Yuasa, Tatsuhiko; Kishi, Masahiko; Ogawa, Emina; Tateno, Fuyuki; Uchiyama, Tomoyuki; Yamamoto, Tatsuya; et al. (Neurourology and urodynamics, 2012)
Objectives To elucidate the pathophysiology of urinary dysfunction in idiopathic normal‐pressure hydrocephalus (iNPH) by single‐photon emission computed tomography (SPECT) and statistical brain mapping. Methods Urinary symptoms were observed and N‐isopropyl‐p‐[123I]‐iodoamphetamine (IMP)‐SPECT imaging was performed in 97 patients with clinico‐radiologically definite iNPH. The patients included 56 men and 41 women; mean age, 74 years. The statistical difference in normalized mean tracer counts was calculated and visualized between patients with urinary dysfunction of severer degrees (>grade 2/4) and milder degrees (<grade 1/4) according to the urinary subscales of the iNPH grading scales. Results There was a significant decrease in tracer activity in the right‐side‐dominant bilateral frontal cortex and the left inferior temporal gyrus in the severe urinary dysfunction group (P < 0.05). In order to minimize the effects of gait and cognitive dysfunction, we performed similar analysis among subjects with little or no such dysfunction, and obtained the same results (P < 0.05) as described above. Conclusions Urinary dysfunction was found to be closely related with right frontal hypoperfusion in iNPH using [123I]‐IMP SPECT. This right frontal area is one of the critical areas for regulating micturition. While secondary incontinence can result from gait disturbance or dementia, there may also be a neurogenic mechanism underlying urinary dysfunction, which is a significant burden in patients with iNPH and their caregivers. Neurourol. Urodynam. 31:50–55, 2012. © 2011 Wiley Periodicals, Inc.